The influence of cissus gum on the mechanical and release properties of paracetamol tablets - a factorial analysis - Adetayo Adeleye; Michael A Odeniyi; Kolawole T Jaiyeoba (São Paulo State University (UNESP), 2010)
The quantitative effects of a new gum, used as a binder, on the mechanical and release properties of paracetamol tablet formulations were analyzed in a 23 full factorial experiment. Cissus gum extracted from Cissus populnea Guill. & Perr. (Vitaceae) was compared with official gelatin. The individual and interaction effects of type of binder, concentration of binder and packing fraction on the friability, tensile strength, brittle fracture index, disintegration time and drug release profile of tablets were determined. Changing the binder from gelatin to cissus gum led to an increase in friability and a decrease in tensile strength, brittle fracture index (BFI) and drug release variables. Increasing binder concentration from 2.0w/w to 4.0%w/w, and increasing relative density from 0.80 to 0.90, led to increases in lamination tendency and release rate of the formulations. Tablets containing gelatin had higher tensile strength, lower friability, longer disintegration time and a greater tendency to laminate than those with cissus gum. Hence, care must be taken in choosing a suitable binder for tablet formulations, with respect to their mechanical and release characteristics. The study suggests that cissus gum should be preferred to gelatin in tablet formulations that tend to cap or laminate or in formulations meant for rapid drug release.